Multi-Scale Organization of the Drosophila melanogaster Genome. - Peterson, S.C.; Samuelson, K.B.; Hanlon, S.L. (Genes, 2021)
Interphase chromatin, despite its appearance, is a highly organized framework of loops and bends. Chromosomes are folded into topologically associating domains, or TADs, and each chromosome and its homolog occupy a distinct territory within the nucleus. In Drosophila, genome organization is exceptional because homologous chromosome pairing is in both germline and somatic tissues, which promote interhomolog interactions such as transvection that can affect gene expression in trans. In this review, we focus on what is known about genome organization in Drosophila and discuss it from TADs to territory. We start by examining intrachromosomal organization at the sub-chromosome level into TADs, followed by a comprehensive analysis of the known proteins that play a key role in TAD formation and boundary establishment. We then zoom out to examine interhomolog interactions such as pairing and transvection that are abundant in Drosophila but rare in other model systems. Finally, we discuss chromosome territories that form within the nucleus, resulting in a complete picture of the multi-scale organization of the Drosophila genome.